2022
DOI: 10.3233/ch-211280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic value of SWE, FNA and BRAF gene detection in ACR TI-RADS 4 and 5 thyroid nodules

Abstract: OBJECTIVES: To compare the diagnostic value of shear wave elastography (SWE), fine needle aspiration (FNA) and BRAF gene detection (BRAFV600E gene mutation detection) in ACR TI-RADS 4 and 5 thyroid nodules. METHODS: SWE images, FNA cytological results and BRAF detection results of ACR TI-RADS 4 and 5 thyroid nodules confirmed by pathology were analyzed retrospectively. The receiver operating characteristic (ROC) curve was drawn to determine the best cutoff value of SWE Emax. In the combined diagnosis of SWE, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Liao et al ( 37 ) found that SWE could be an independent predictor for malignant thyroid nodules; the sensitivity and specificity were 81% and 65%, respectively, with the best cutoff of Emean being 32 kPa. In this study, we found that SWE was useful in the differentiation of benign and malignant ACR TI-RADS 4 and 5 category thyroid nodules, which was consistent with a previous study ( 35 – 37 ), and HT did not seem to affect the stiffness of thyroid nodules. Compared with Emin, Emean, and Eratio, Emax >46.8 kPa had the best diagnostic performance for ACR TI-RADS 4 and 5 category thyroid nodules coexisting with HT in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Liao et al ( 37 ) found that SWE could be an independent predictor for malignant thyroid nodules; the sensitivity and specificity were 81% and 65%, respectively, with the best cutoff of Emean being 32 kPa. In this study, we found that SWE was useful in the differentiation of benign and malignant ACR TI-RADS 4 and 5 category thyroid nodules, which was consistent with a previous study ( 35 – 37 ), and HT did not seem to affect the stiffness of thyroid nodules. Compared with Emin, Emean, and Eratio, Emax >46.8 kPa had the best diagnostic performance for ACR TI-RADS 4 and 5 category thyroid nodules coexisting with HT in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with SE, SWE is less influenced by the experience and operation of the operator. Zhang et al ( 35 ) found that SWE had high diagnostic efficiency for ACR TI-RADS 4 and 5 category thyroid nodules; the accuracy was 76.1%, with the best cutoff of Emax being 40.9 kPa. Chen et al ( 36 ) conducted a meta-analysis with 4,296 thyroid nodules and found that Supersonic shear imaging showed high accuracy in the differentiation between benign and malignant thyroid nodules, which could serve as a noninvasive and important tool for thyroid nodule evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this may be ethnic differences mentioned above and other non-classical PTC subtypes which seldom carry BRAF mutation. The specificity of BRAF mutation detection is reported ranging from 88.7% to 100%, 27,28 and some studies have found that few cases with BRAF mutation were not PTC in postoperative histology. 29 The specificity in this study is slightly lower, which may be correlated with not enrolling follow-up benign patients.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Some studies suggested that TI-RADS combined with SWE was an effective diagnostic method. [3,[13][14][15][16] However, due to the influence of the acoustic shadow of the trachea, the elasticity value for thyroid nodules adjacent to the trachea or blood vessels could not be accurately measured in the 2D plane. Yang et al [17] believed that the elasticity score obtained by 2D-SWE elastography and the elasticity ratio obtained by pressure elastography were limited in the differential diagnosis of thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%